PENGARUH PENGETAHUAN JENIS KONTRASEPSI DAN KONSUMSI PROTEIN TERHADAP PRODUKSI AIR SUSU IBU MASA NIFAS - Abrori; Budiastutik, Indah; Marsela, Novia (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2015)
Background: the big issue reports on the achievement of the Millennium Development Goals (MDGs) among them; the low nutritional status, health of pregnant women, mothers and infants deaths caused by infection of the postpartum period. The main basic need to be aware of how mom is nutrition. A mother eating a balanced diet with the recommended, enough carbohydrates, proteins, fats, vitamins and minerals. But the problem of the shortage of animal protein and vegetable consumption affect production of breast milk on the first day of a thousand births. Breast feeding himself became an effective contraceptive method, known as the method of Amenorea Lactation (MAL). Intent and knowledge is the solution for those who have problems in breast feeding. Aim: This study aimed to discover the correlation of knowledge, types of contraception,and protein intakeonbreast milk productionduringpost partum period at Puskesmas Beduai Kabupaten Sanggau Kapuas. An observational method, as well as a cross sectional approach, was carried out in this study. The samples were 89 mothers. While the instruments were questionnaires and observation sheets. The data were statistically anlyzed by using chi suare test. Findings: The study revealed that the respondents were lack of knowledge on breastmilk production during postpartum (47.4%), used injectable contraception (51,7%), did not consume vegetable protein (56,2%), did not consume animal protein (60,7%), and had adequate breastmilk production . Thus, there were no correlation of knowledge (p=0,352), vegetable protein intake(value=0,407), animal protein intake (value=0,559), and breast milk productionduringpost partum period. However, there was correlation of types of contraception (value=0,033; OR=0,377) and breast milk productionduringpost partum period. Conclusion: There is no relationship between the knowledge with the production of breast milk during childbirth; the majority of respondents who use the birth control pills and syringe of type. There is no relationship between the consumption of vegetable protein with the production of breast milk; There is no relationship between the consumption of animal protein with the parturition period breast milk production Suggestions: Postpartum mothers should enhance their knowledge and understanding about breastfeeding production and types of contraception for breastfeeding mothers through mass,electronic, and printed media.